Prevalence of peripheral neuropathy and peripheral artery disease in diabetic patients attending a tertiary care hospital - Meena, Sangeetha; C., Manikandan R. (International Journal of Advances in Medicine, 2019)
Background: Foot complications are one of the most devastating complications among diabetes all over the world. Both Diabetic Peripheral Neuropathy (DPN) and Peripheral Artery Disease (PAD) are responsible for diabetic foot complications. Aim of this study is to screen diabetic patients for both DPN and PAD. Methods: This is a cross-sectional study covering 200 diabetic patients attending a Teaching Hospital. Prevalence of DPN was assessed using Biothesiometer and PAD by measuring the Ankle Brachial Index using handheld Doppler. Results: 49.5% had DPN and 19.5% had PAD. 13% had both PAD and DPN. Most of the subjects were in 51-60 years age group constituting 36.5 %. 61.5% were females. 69.5% had diabetes for more than 10 years. 88% had their HbA1C of more than 6.5%. Conclusions: The prevalence of PVD is multi-fold higher in patients with diabetes with smoking, hyperglycemia, hypertension, dyslipidemia, as major risk factors. Ankle, brachial pressure index, is useful in identifying PVD and it needs further evaluation by an arterial color Doppler and digital subtraction angiography.